Pavilion of women - Buck, Pearl S. (Pearl Sydenstricker), 1892-1973. (Berkeley, CA : Distributed in North America by Publishers Group West, 1974)
Nobel Prize-winning American author Pearl Buck's 1946 novel about a Chinese woman who decides to leave her marriage on her fortieth birthday, choosing a concubine for her landed-class husband and moving on to a life of freedom.
Adult
Keywords: Family -- China -- Fiction; Married women -- China -- Fiction; Family life -- China -- Fiction; Wives -- China -- Fiction; China -- Fiction; China -- Fiction